African labour survey - International Labour Office (Geneva : International Labour Office, 1958)
The survey is designed to serve three related but distinct purposes. The first is, it is important to have an objective and authoritative a picture as possible of the existing situation, and to provide a point of departure for the future work of ILO in this field. Secondly an African labour survey prepared to draw on the knowledge of employers and workers as well as on governmental and unofficial experience and should be prepared with full regard to conditions special to Africa. Thirdly ILO should contribute to making the problems within its purview which arise in Africa more fully understood throughout the world.
Includes bibliographical references: p. 695-707.
rpm 23/02/2018
Loans
Keywords: Labor and laboring classes